The influence of pay, career growth and job security among Gen-Y toward intention to leave at FM company - Nor Aleyamira, Ahmad Faizol (2017)
This study was conducted to investigate the influence of pay, career growth and job security toward intention to leave among Gen Y at FM Company, Johor Bahru. This research was conducted due to high turnover rate reported among Gen Y employees in FM Company, Johor Bahru. The main aim of the study was to identify the relationship of pay, career growth and job security with intention to leave. This study was done through quantitative method in which questionnaires were used as a medium to collect data. A total of 100 questionnaires were distributed to respondents, however only 80 questionnaires were usable for further analysis. Data then were analyzed by Statistical Package for Social Science (SPSS) version 22.0 using Reliability Analysis, Correlation Analysis and Multiple Regression. The result showed only pay and career growth was significantly positive with intention to leave while job security was not significantly influence to intention to leave.